Mathematical model of the reliability transceiving apar in the receiving mode according to the criterion of permissible degradation of the side lobe level - Костановський, В. В.; Козачук, О. Д.; Мачалин, І. О. (Science-based technologies, 2020)
The article discusses a mathematical model of the reliability of APAR of multifunctional radars in the receiving mode according to the criterion of permissible deterioration of the side lobe level. To determine the level of the side lobes (quantization of phase shifters) of a flat APAR with a uniform amplitude distribution, the formula proposed by prof. R.S. Hansen in Phased Antenna Arrays. Using this formula, the graphs of the dependences of the logarithm of the root mean square value (rms) of the side lobe level due to the random phase quantization error on the number of emitting elements in the APAR, depending on the logarithm of the number of emitting elements in the APAR, are presented. A polynomial approximation of the side-lobe level from the relative level of the number of failed transmit-receive channels is used to construct a reliability model for APAR. In this work, a two-level structural diagram of the APAR reliability and a transcendental equation are constructed, the solution of which allows us to determine the mean time to failure of the AESA by the criterion of the permissible deterioration of the side lobe level. Formulas are presented for determining the probability of failure-free operation, the density of the distribution of failures and the failure rate of the APAR in the receiving mode. An illustrative example of calculating the reliability indices of a flat APAR in the receiving mode for 6400 transmitting and receiving channels is considered. The results presented in the article can be used by scientists and development engineers in the design of multifunctional radars with AFAR, as well as in the educational process.